GAMBARAN PENGETAHUAN TENTANG COVID-19 DAN SIKAP MAHASISWA REKAM MEDIS DAN INFORMASI KESEHATAN UNIVERSITAS ESA UNGGUL TERHADAP PROTOKOL KESEHATAN DALAM MENGHADAPI MASA PANDEMIC COVID-19 - Ratna Sari; Puteri Fannya; Nanda Aula Rumana; Wiwik Vitianingsih (Nusantara Hasana Journal, 2022)
The implementation of health protocols plays a crucial role in handling the Covid-19 pandemic. Breaking the chain of spread of Covid-19 is the main key to handling the Covid-19 pandemic. This can be achieved by implementing massive health protocols that are universally adhered to by all components of society. The successful implementation of this health protocol will drastically reduce the number of hospitalizations for Covid-19 patients with severe symptoms. Thus, the burden on health care facilities is reduced drastically and health workers can focus on palliative care for patients with moderate to severe symptoms. The scope of this research is the knowledge and attitudes of students towards health protocols in the Student Medical Record and Health Information study program at Esa Unggul University, Kebon Jeruk which will be held in December 2021. Which aims to find out how the description of knowledge about covid-19 and the attitude of Medical Record and Health Information students at Esa Unggul University towards health protocols in dealing with the covid-19 pandemic period. By using a quantitative descriptive method with a cross sectional approach with the sampling technique in this study using the Slovin formula. Based on the results of research conducted on 186 respondents, researchers found that the description of the level of student knowledge of health protocols in dealing with the Covid-19 pandemic was in the good category with a percentage of 98.4%. health protocols are included in the positive category with a percentage of 98.4%. The advice from the author is for students of medical records and health information at esa superior university to remain disciplined in implementing good and correct health protocols that have been set by the government in order to reduce the spread of the Covid-19 virus directly or indirectly.